Financial Feasibility Analysis of Islamic-Based International School Investment in East Bandung - Mutiah Qur'aniah; Neneng Susanti (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: Research This aims to determine the feasibility of the construction project for an Islamic-based International Middle School in the East Bandung area. reviewed from the financial aspect analyzed using the Net Present method Value, Internal Rate of Return, Benefit Cost Ratio, Profitability Index, Payback Period and Debt Service Coverage Ratio. Methodology Research: Research This study uses quantitative research methods. The data sources used are primary and secondary. Data collection methods include interviews, and research. The population in this study were parents of 12-year-old students in East Bandung, with a sample of 100 people using the Solvin formula. Sampling was done using random sampling. Results: Analysis? finance show NPV > 0, namely Rp. 38,651,935,498, IRR > WACC, namely 47 %, BCR ? 1 is 3.56, P I ? 1 is 5.54, PP for 2 years 5 months, and DSCR ? 1, namely 15.70. Conclusions: Findings the confirm that project the worthy in a way financial and operational, supported by strong market potential and prospects term sustainable length.? Limitations: This study depending on projected demographic and financial data, which may influenced by dynamics economics, regulations, or social in the future. Contributions: Research This offer outlook valuable for investors, educators, and creators policy, providing runway based proof for decision investment education and contribute to development education school medium on based on Islam in Indonesia.